Union presidential and parliamentary elections in Tanzania 29 October 1995 (Commonwealth Secretariat LondonGB, 1996)
Presents the political background. Looks at aspects such as the legal and administrative; preparations for the elections; and, the campaign. Examines the role of the media and focuses on the poll and the count. Presents conclusion.
DC